TNF-α response in macrophages depends on clinical Legionella pneumophila isolates genotypes. Issue 1 (31st December 2022) - Guillemot, Johann; Ginevra, Christophe; Allam, Camille; Kay, Elisabeth; Gilbert, Christophe; Doublet, Patricia; Jarraud, Sophie; Chapalain, Annelise
ABSTRACT: Legionnaires' Disease (LD) is a severe pneumonia mainly caused in Europe by Legionella pneumophila serogroup 1 (Lp1). Sequence-based typing methods reveal that some sequence types (ST) are overrepresented in clinical samples such as ST1 and ST47, suggesting that some strains are more fit for infection than others. In the present study, a collection of 108 Lp1 clinical isolates were used to evaluate the strain-dependent immune responses from human macrophages. Clinical Lp1 isolates induced differential TNFα secretion from macrophages. ST1 isolates induced a significantly higher TNF-α secretion than non-ST1, whereas ST47 isolates induced a significantly lower TNF-α secretion than non-ST47 isolates. ST1 isolates induced a significantly higher cell death than ST47 isolates evaluated by lactate dehydrogenase activity (cytotoxicity) and caspase-3 activity (apoptosis). Treatment of macrophages with anti-TNF-α antibodies significantly reduced the cell death in macrophages infected with ST1 or ST47 strains. The TNF-α secretion was neither explained by a differential bacterial replication nor by the number or type (bystander or infected) of TNF-α producing cells following infection but by a differential response from macrophages. The Paris ST1 reference strain elicited a significantly higher TNF-α gene transcription and a higher induction of NF-κB signaling pathway than the Lorraine ST47 reference strain. Clinical Lp1 isolates induce a diverse immune response and cell death, which could be related to the genotype. The two predominant sequence-types ST1 and ST47 trigger opposite inflammatory response that could be related to the host susceptibility.